Graphene quantum dots assisted exfoliation of atomically-thin 2D materials and as-formed 0D/2D van der Waals heterojunction for HER - Gong, Jun (2022)
Atomically-thin 2D materials have changed the landscapes of many fields. Their applications however are limited by lack of methods for readily and scalable production with high quality. Herein, a simple strategy is reported to exfoliate pristine single or few-layered 2D materials (MoS2, h-BN, WS2, g-C3N4 microsheets) using bottom-up grown amphiphilic graphene quantum dots (GQDs) as both the intercalation agent and dispersant. Further, it is shown that the as-formed GQD/MoS2 van der Waals heterojunctions (vdWHs) give enhanced performance for electrocatalysis of hydrogen evolution reaction (HER) owing to the synergistic coupling at the 0D/2D heterojunction, delivering a current density of 10 mA cm−2 at a low overpotential of 160 mV with a small Tafel slope of 56.9 mV dec−1. In addition to providing a new method for preparing ultrathin 2D microsheets, this study unleashes the application potential of 2D materials and GQD-based 0D/2D vdWHs as non-precious electrocatalysts.